2018
DOI: 10.20491/isarder.2018.495
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of Non-Performing Loans: Case of Turkey and Saudi Arabia

Abstract: Non Performing loans (NPLs) are important variables on a macro scale for the financial stability of the country as well as microscale for banks profitability itself. Since 2008 global crisis, NPLs are monitored worldwide and became systemically important. In this research, by using a data set between 2000-2016, the macroeconomic determinants of NPLs have been investigated for Turkey and Saudi Arabia. By using NPL ratio as the dependent variable and estimating through beta regression analysis, it is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
1
0
6
Order By: Relevance
“…Luchando por su participación en el mercado, los bancos comenzaron a otorgar préstamos en condiciones más relajadas y aumentó la proporción de préstamos morosos y, consecuentemente, también el riesgo crediticio (Ristić y Jemović, 2021). Desde la crisis mundial de 2008, los préstamos morosos se controlan en todo el mundo y se tornaron importantes (Polat, 2018). La calidad de las exposiciones crediticias y su relación con el ciclo de la economía ha sido estudiada desde distintas perspectivas.…”
Section: Revision De Literaturaunclassified
See 3 more Smart Citations
“…Luchando por su participación en el mercado, los bancos comenzaron a otorgar préstamos en condiciones más relajadas y aumentó la proporción de préstamos morosos y, consecuentemente, también el riesgo crediticio (Ristić y Jemović, 2021). Desde la crisis mundial de 2008, los préstamos morosos se controlan en todo el mundo y se tornaron importantes (Polat, 2018). La calidad de las exposiciones crediticias y su relación con el ciclo de la economía ha sido estudiada desde distintas perspectivas.…”
Section: Revision De Literaturaunclassified
“…Por su parte, Polat (2018) El deterioro de la calidad de la cartera de los préstamos bancarios ha estado en el centro de episodios de costosos problemas para el sistema bancario y crisis económicas tanto en las economías avanzadas como en desarrollo (Nkusu, 2011). Diversas investigaciones demuestran que el comportamiento de la economía influye en el cumplimiento de los usuarios de los créditos, por lo cual, se destaca la importancia del estudio de las variables macroeconómicas que expliquen las afectaciones a la cartera de crédito, como son el PIB, la inflación, la tasa de interés, tasa de desempleo, entre otros.…”
Section: Revision De Literaturaunclassified
See 2 more Smart Citations
“…The effects of non-performing loans on financial stability was examined in comparison with the 2000-2016 period data in Turkey and Saudi Arabia by Polat (2018). In the study, for Turkey, it was found that there is a positive relationship between GDP, market capitalization, inflation rate and nonperforming loans ratio.…”
Section: -Literature Reviewmentioning
confidence: 99%